(untitled) (Itinera, 2020)
The essay attempts to analyze the relationship between power and image. The writing starts with the studies of Alberto Giacometti between 1956 and 1961 for the portrait of the Japanese philosopher Isaku Yanaihara. Giacometti says that in this experience one of his tasks is grasping the triangular and pyramidal shape of the portrayed nose. This image, reminiscent of Egyptian pyramids as graves and representations of the pharaoh’s power, becomes vitalist shape, hanging between life and death. Power, required to be efficient, deals with what is subject to its force; its exertion doesn’t move, it can protect but doesn’t save; it hardly gives way to nothing. Power aims at simplification, while art amplifies existence complexity and variety. Art can allows itself a wait and consents to unproductiveness, it strives to bring life into death. Works of art give a picture of power that is not afraid of generating and destroying itself to be able to start again. Works of art have to disown every seeming final goal to avoid their imprisonment into the shapes produced by the desire itself.